Scattering-induced entanglement between spin qubits at remote two-state structures. - Habgood, M; Jefferson, J; Briggs, G (2009)
A theoretical scheme is presented for the entanglement of two-electron spin qubits bound in series within a quasi-one-dimensional mesoscopic structure at a distance beyond their normal range of interaction. A third electron is scattered from them, and full entanglement is achieved upon measurement of a transmitted electron in the correct spin state. Critically, each bound electron is trapped within an individual structure that has at least two spatial states. Two simple examples of such structures are discussed here. One is a 'stub', in which a quantum dot (for example) is coupled to one side of the quasi-one-dimensional structure. The other is a pair of degenerate, coupled quantum dots, with strong interdot Coulomb repulsion, placed within the one-dimensional superstructure. Both of these are shown to allow generation of entanglement with a significant probability of success. In contrast to the results of the authors' previous works, this allows for the generation of entanglement in a series, rather than in a parallel, configuration of the bound electrons with respect to the propagating electron.